Marketing efficiency of red chilli pepper in North Sumatera Province. Issue 2 (June 2021) - Nasution, A H; Hanter,; Rahman, P
Abstract: This study aims to analyse the marketing of red chili pepper using price efficiency analysis. The data used is secondary data, namely time series data of monthly red chili pepper prices at the level of farmers, intermediate traders, wholesalers, retailers and consumers during 2015 to 2019. Data processing was carried out using quantitative descriptive analysis. Based on the results of the price efficiency analysis conclude that in the short and long term the red chili pepper market at the farm level is strongly intermediate traders, wholesalers, retailers and consumers. This can be seen from the IMC value which is smaller than 1 and the coefficient b2 which is greater than 0.05. This integration shows the marketing of red chilies in North Sumatra is efficient when viewed from price efficiency.